The Portrayal of Women In Electronic Media - Ragam. S, Padma; Jennifer G Joseph, Dr. (International Journal of Engineering and Technology, 2018)
We feel that women are free from the clutches of men and empowered completely but they are not completely empowered.Â In this male dominated society, the status of the women are still inferior to men. They try to stereotype the image of women.Â Â In the same manner womenâ€™s images are projected and portrayed negatively in the media. Her real life experience is rarely portrayed in media but it is exaggerated in all the fields. Â Â